Repair overlays of modified polymer mortar containing glass powder and composite fibers-reinforced slag: mechanical properties, energy absorption, and adhesion to substrate concrete - Momeni, Komeil; Vatin, Nikolai Ivanovich; Hematibahar, Mohammad; Gebre, Tesfaldet Hadgembes (Frontiers in Built Environment, 2024)
This article aims to investigate the mechanical properties and substrate adhesion of the pull-off method in polymer mortars modified with styrene-butadiene resin polymer (SBR) containing glass powder and composite fiber-reinforced slag. Different mix designs were investigated with and without SBR, taking into account different amounts of glass powder and slag separately and in combination, along with the effect of glass, polypropylene, and steel fibers alone and in combination. The flexural performance and energy absorption of beams retrieved with these layers were also assessed. The results revealed significant differences and increases in the substrate adhesion of the restored modified polymer layers containing SBR compared to the polymer-free repair overlays. Furthermore, an improvement was observed in the adhesion performance of the repair overlay using a combination of slag and glass powder and the glass and polypropylene fiber composite. The highest adhesion was related to the modified polymer mortar design containing composite fibers of glass, polypropylene, and steel with 25% replacement of SBR polymer for 10% glass powder, 10% slag, and 5% slag with 5% glass powder. The adhesion was increased by about 3.74, 3.72, and 3.78 times compared to the repair overlay of the control design. Modified polymer mortars had a higher T150D toughness. Moreover, the energy absorption was significantly improved by the presence of SBR polymer. The highest toughness values were found in the beams restored with modified polymer mortars containing polypropylene, glass, and steel composite fibers with an increase of 48.51%–66.42% compared to the samples without polymer as a result of the pozzolans used in this mix.